A Preliminary study on the treated charcoal development from OPEFB for phenolic compound remova - Rohaya Binti Hitam (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Treated charcoals derived from oil palm empty fruit bunch (OPEFB) were investigated to find the suitability of its application for removal of phenolic compound in aqueous solution through adsorption process. For the production of treated charcoals, the type of treatment used is chemical activation by using two dehydrating agents which are potassium hydroxide (KOH) and phosphoric acid (H3PO4). A control (untreated OPEFB) was used to compare the adsorption capacity of the treated charcoals produced from the process. The characteristics of the treated charcoals were determined by using SEM, FTIR and BET. The analysis of SEM show H3PO4 treated charcoal have very clear pores before the adsorption and the pores is occupied by phenolic compound molecules after the adsorption. The FTIR analysis indicated the presence of C-H bond and N-H bond in all adsorbents while BET analysis found the H3PO4 treated charcoal have the largest surface area compared to the other charcoals. Furthermore, the results also indicated that the treated charcoal derived by H3PO4 solution showed better adsorption capacity compared to the other in the aqueous solution of phenolic compound. It was observed that the adsorption capacity was higher at low pH (2-5) and higher value of initial concentration of phenolic compound (20-100 mg/L). The adsorption isotherm study showed that the data is fitted better with Langmuir adsorption isotherm compared to the Freundlich. Kinetic and thermodynamic studies of 2-chlorophenol adsorption onto H3PO4 treated charcoal also studied to evaluate the adsorption rate and condition of the process. From the kinetic study, pseudo-second order successfully describes the kinetics of 2-chlorophenol adsorption onto H3PO4 treated charcoal.